"...porque ninguna es perfecta si hemos de hablar por lo claro": un retrato de las mujeres en la literatura colonial costarricense - Sancho Dobles, Leonardo (2014)
In one of the three short theatrical plays, written by Joaquín de Oreamuno and Muñoz de la Trinidad and represented in de city of Cartago in 1809, it is made a physical description of women that could be well classified as a literary portrait. In this portrait it is mentioned from head to toes and gives valuable information of the uses and cultures of the time. From the parliaments of this theatrical piece, in this opportunity it is described the uses and cultures of the Costa Rican society in the colonial period.